Dengue virus type 3 in Brazil: a phylogenetic perspective - Josélio Maria Galvão de Araújo; Gonzalo Bello; Hermann Gonçalves Schatzmayr; Flávia Barreto dos Santos; Rita Maria Ribeiro Nogueira (Memorias do Instituto Oswaldo Cruz, 2009)
Circulation of a new dengue virus (DENV)-3 genotype was recently described in Brazil and Colombia, but the precise classification of this genotype has been controversial. Here we perform phylogenetic and nucleotide-distance analyses of the envelope gene, which support the subdivision of DENV-3 strains into five distinct genotypes (GI to GV) and confirm the classification of the new South American genotype as GV. The extremely low genetic distances between Brazilian GV strains and the prototype Philippines/L11423 GV strain isolated in 1956 raise important questions regarding the origin of GV in South America.